IMPLEMENTASI NILAI-NILAI HADITS DALAM PEMBINAAN PERILAKU DISIPLIN PESERTA DIDIK DI MA DARUL ULUM PURWOGONDO - Suci Romadhona; Ana Rahmawati (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to examine the implementation of hadith values, particularly the leadership hadith (Bukhari No. 7138) and the prayer-command hadith (Abu Dawud No. 495), in fostering disciplined behavior among students at MA Darul Ulum Purwogondo. A qualitative approach was employed, involving interviews with the head of madrasah, the Qur'an-Hadith teacher, and the guidance counselor, along with direct observation of instruction and disciplinary practices. Findings show that hadith values are implemented through a cognitive pathway, involving lesson-planned instruction on responsibility (amanah) and habituation embedded in the eleventh and tenth grade lesson plans, and a structural pathway comprising a tiered disciplinary system that combines digital attendance monitoring with a graduated sanction mechanism, ranging from verbal warnings to home visits, evaluated regularly through teacher meetings. Nevertheless, of approximately 600 students, 25% had committed violations, revealing a persistent gap between students' cognitive understanding of the hadiths and their consistent practice, largely driven by peer influence, smartphone use, and insufficient parental supervision. The study recommends strengthening synergy between the madrasah and families so that hadith values move beyond cognitive knowledge into sustained disciplined behavior.